Cover Image, Volume 27, Issue 9. Issue 9 (September 2017) - Hurst, Katrina; Badgley, Corinne; Ellsworth, Tanner; Bell, Spencer; Friend, Lindsey; Prince, Brad; Welch, Jacob; Cowan, Zack; Williamson, Ryan; Lyon, Chris; Anderson, Brandon; Poole, Brian; et al.
Abstract : Cover legend: This cover image, by Katrina Hurst et al., is based on the Research Article A putative lysophosphatidylinositol receptor GPR55 modulates hippocampal synaptic plasticity, DOI:10.1002/hipo.22747 .